2020
DOI: 10.1002/art.41388
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of COVID‐19 in Patients With Rheumatic Diseases Treated With Targeted Immunosuppressive Drugs: What Can We Learn From Observational Data?

Abstract: Objective. To describe the incidence and severity of coronavirus disease 2019 (COVID-19) in patients with rheumatic diseases treated with targeted synthetic or biologic disease-modifying antirheumatic drugs (DMARDs) compared with that in the general population living in the same Italian region. Methods. Patients followed up at 2 rheumatology referral centers in Lombardy from February 25, 2020 to April 10, 2020 were invited to participate in a survey designed to identify patients who had confirmed COVID-19, clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
101
4
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 15 publications
12
101
4
5
Order By: Relevance
“…Drug shortages and altered patterns of health care have been concerning since the early days of this pandemic [16]. Several reports point to the fact that prevalence and severity of COVID-19 seem not to be higher in rheumatic patients, even those under treatment with immunosuppressants, biologics, and small molecules, than those found in the general population [17][18][19][20]. This could be different for some conditions.…”
Section: How Does Covid-19 Affect Rheumatology Practice?mentioning
confidence: 99%
“…Drug shortages and altered patterns of health care have been concerning since the early days of this pandemic [16]. Several reports point to the fact that prevalence and severity of COVID-19 seem not to be higher in rheumatic patients, even those under treatment with immunosuppressants, biologics, and small molecules, than those found in the general population [17][18][19][20]. This could be different for some conditions.…”
Section: How Does Covid-19 Affect Rheumatology Practice?mentioning
confidence: 99%
“…The effect of gender has not been specifically explored in rheumatic diseases compared with the general population. [103][104][105][106] The clinical features of COVID-19 are similar in patients with RD. There is a higher risk of intensive care unit (ICU) admission and respiratory failure in patients with RD who develop COVID-19 compared with controls.…”
Section: Scientific Statements In Rheumatological Diseases With Covid-19mentioning
confidence: 93%
“…This could also contribute to the low incidence in this population. 10 A study from Spain reported a 1.32-fold higher risk of PCR positive COVID-19 requiring hospital admission in chronic inflammatory diseases compared with general population. The risk was however variable, depending on the disease and treatment.…”
Section: Covid-19 In Rheumatic Diseases (Rd)mentioning
confidence: 99%
“…The incidence of COVID-19 in RD was found to be similar to the general population in the same region in two studies from Italy. 10,11 Patient with RD exerted due diligence when it came to preventive measures. This could also contribute to the low incidence in this population.…”
Section: Covid-19 In Rheumatic Diseases (Rd)mentioning
confidence: 99%
See 1 more Smart Citation